ОЦЕНКА СРОКОВ СЛУЖБЫ ЭЛЕКТРОДВИГАТЕЛЕЙ, РАБОТАЮЩИХ В ПОВТОРНО-КРАТКОВРЕМЕННЫХ РЕЖИМАХ - Федоров, М.М.; Лужнев, А.И.; Боев, А.Е. (Інститут електродинаміки НАН України, Київ, 2012)
This paper presents results of researches of intermittent mode ratings influence on thermal state and insulation lifetime of asynchronous motor. It is shown that short-term overheating in steady-state regime has an essential impact on insulation thermal aging and should be taken into account for electric motors in intermittent modes. References 6, table 1, figures 4.